2018
DOI: 10.1159/000492323
|View full text |Cite
|
Sign up to set email alerts
|

A Matter of Rules? A Longitudinal Study of Parents’ Influence on Young People’s Drinking Trajectories

Abstract: Based on longitudinal survey data (2005, 2008, 2015), this paper investigates binge drinking among young people in Denmark. We analyse the relationship between parental alcohol rules in 2005 and the development of their children’s heavy episodic drinking from age 15 to 25/26 using a multilevel approach to repeated measures. Two hypotheses are tested. The first is that young people from families with “strict” alcohol rules have a lower level of binge drinking than young people from families with lenient rules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Similarly, past research has shown positive correlations between parental education (which is in part influenced by genetic factors that are passed on to offspring) and adolescent alcohol use (Bachman et al, 1981;Zucker & Harford, 1983). A possible interpretation is that the same genetic factors that give rise to a positive educational environment could contribute to greater access to alcohol in the home as a result of more highly educated parents having more disposable income, a factor that has been found to predict greater adolescent alcohol use (Bellis et al, 2007;Lintonen & Nevalainen, 2017;Østergaard et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, past research has shown positive correlations between parental education (which is in part influenced by genetic factors that are passed on to offspring) and adolescent alcohol use (Bachman et al, 1981;Zucker & Harford, 1983). A possible interpretation is that the same genetic factors that give rise to a positive educational environment could contribute to greater access to alcohol in the home as a result of more highly educated parents having more disposable income, a factor that has been found to predict greater adolescent alcohol use (Bellis et al, 2007;Lintonen & Nevalainen, 2017;Østergaard et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…The factors relating to the family and friends included parental drinking or poor relationships with parents [ 8 , 9 ], parents’ recommendations of alcohol consumption [ 10 ], the number of friends who drank with, frequency of friends’ drinking, and amount of alcohol that they consumed [ 7 ]. Parents’ recommendation to drink in childhood displayed a particularly significant association with an increased likelihood of risky drinking later in adolescence [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This research provides a strong rationale for prevention based on family-associated risk and resilience factors [15][16][17]. For example, parents influence their offspring's substance use by their own substance use, by setting alcohol-related rules and norms, and by monitoring children's whereabouts [18]. Moreover, parents contribute substantially to the development of self-regulation, psychological functioning, and adaptive strategies for managing negative emotions [19,20].…”
Section: Introductionmentioning
confidence: 99%